2023
DOI: 10.1002/admi.202202256
|View full text |Cite
|
Sign up to set email alerts
|

Probing transport energies and defect states in organic semiconductors using energy resolved electrochemical impedance spectroscopy

Abstract: will occur. Additionally, probing the DOS with high enough sensitivity to probe defect states is important, as these defect states often limit charge transport in semiconducting materials or serve as recombination centers in photovoltaics. [3,5,6] Recently, an electrochemical technique, energy-resolved electrochemical impedance spectroscopy (ER-EIS), was applied to measure the density of states of organic semiconductors (OSCs) with high sensitivity. [7][8][9][10][11] The detection of defect states using electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…featureless, indicating well-mixed layers of P3HT and PCBM. PCBM crystals can be noticeably seen in the annealed films, as evident by their redshifted emission peaks compared to the rest of the film [67][68][69]. In the darker regions, especially in the annealed P3HT-II:PCBM film, some contrast can be seen, which indicates disordered and ordered P3HT phases.…”
Section: Optical Propertiesmentioning
confidence: 92%
See 1 more Smart Citation
“…featureless, indicating well-mixed layers of P3HT and PCBM. PCBM crystals can be noticeably seen in the annealed films, as evident by their redshifted emission peaks compared to the rest of the film [67][68][69]. In the darker regions, especially in the annealed P3HT-II:PCBM film, some contrast can be seen, which indicates disordered and ordered P3HT phases.…”
Section: Optical Propertiesmentioning
confidence: 92%
“…It was reported that the ER-EIS method is instrumental not only to detemine the DOS distribution of neat organic films but also their blends [57,[65][66][67]. Therefore, this method was employed for P3HT-I:PCBM and P3HT-II:PCBM blends on both non-annealed and annealed films to delineate DOS changes due to variations in the fabrication process of the active layer.…”
Section: Density Of States Distributionmentioning
confidence: 99%
“…The raw data from the lock-in were then processed by normalizing them to the lamp power spectrum. Further details of the PDS apparatus can be found in the literature …”
Section: Methodsmentioning
confidence: 99%
“…Further details of the PDS apparatus can be found in the literature. 34 Thin films for the PDS measurements were prepared on clean quartz substrates. The perovskite films were fabricated by using the same procedure mentioned above with 0.6 M precursor solutions and 6000 rpm spin speed.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was reported that ER‐EIS is sensitive not only to transport but also to defective electronic states, thereby showing promise for the study of degradation in organic films. [ 117,120 ] With respect to the PM6:Y6 solar cells, oxidation of PM6 was observed to take place rather quickly upon sample exposure to the O 3 atmosphere. This resulted in a significant rise in the defect density near the polymer HOMO and a downward shift of the LUMO energy (Figure 12d).…”
Section: Impedance Spectroscopy Insights From the Studies Of Pm6:y6mentioning
confidence: 99%